CIPP evaluation model for the coaching program of running athletes - Aldapit, Eki; Suharjana, Suharjana (Psychology, Evaluation, and Technology in Educational Research, 2019)
This study aimed to evaluate the training programs of sprinting, middle distance running, and long distance running athletes. This type of research is the study evaluation using CIPP models. The approach used in this study is a qualitative approach with qualitative data analysis model of Miles & Huberman. The results of the evaluation include: (1) context Â evaluation shows that there are lack of budget, facilities, governmentâ€™s support, sponsorship, health experts, test instrumens and test spaces, (2) evaluation of the inputt indicates there is a lack of facilities and infrastructure as the main support of the running track, (3) evaluation of the process demonstrates the ability of trainers to implement the training process is very helpful to the achievement of a good coaching program and achievements of athletes. The recruitment of athletes should be open to all people, so there should not be the impression of nepotism and collusion, (4) evaluation of the product shows the achievements have been at national and international level. Achievement would be better and more sustainable if supported by a context and a perfect addition of the input to the process which has been good.